COMPARISON OF DIAGNOSTIC EFFICACY OF RAPID DIAGNOSTIC DEVICES FOR DENGUE VIRUS INFECTION-A PIOLT STUDY - Yusuf, Noshin Wasim; Kausar, Naeem; Akbar, Roheena; Iqbal, Nasir (Journal of Ayub Medical College Abbottabad, 2008)
Background: To compare the diagnostic efficacy of commercially available rapid diagnostic test devices for Dengue serology. To find out the sensitivity and specificity of rapid diagnostic devices with Elisa results as the Gold standard. Methods: During the dengue virus epidemic in Lahore a pilot study was conducted in order to evaluate the diagnostic efficacy of two most frequently used immunochromatographic rapid test devices in public sector hospitals. The results of both the kits were compared to each other. Sensitivity and specificity was calculated against results of ELISA as the reference gold standard. Results: Results of kit-A revealed a very high false negative rate when compared to ELISA where actual prevalence rate shown by ELISA was 96.0% compared to prevalence rate of 44.0% with rapid diagnostic test device kit-A. Similarly the results of rapid test device Kit-B showed high false negative results for dengue virus prevalence. Actual prevalence rate of dengue fever shown by ELISA was 96.0% where as it turned out to be 50% with the kit-B rapid test device. Comparison of Results of two kits revealed no significant difference of test positivity rates. Conclusion: Rapid test devices based on immunochromatographic method supplied in the public sector hospitals are not reliable diagnostic tools for screening for dengue virus infection Health authorities need to review their strategy for supply of more reliable tools during epidemics in order to avoid false negative results. Keyword: Immunochromatographic rapid test, Dengue virus, ELISA, Screening tests